Creativity Development Of Early Grades Elementary School Teachers In Learning Activities - Miftachudin Miftachudin (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2022)
The purpose of this research is the importance of creativity development of early grades elementary school teacher in learning activities to improve student creativity. Learning activities aim to make children able to achieve the learning goals. Impressive learning will encourage children’s enthusiasm to study well. This paper is qualitative research, where the data are obtained from observation, interview, and documentation. The results of this study indicate four aspects of creativity. First, the personal aspect, creative teachers are people who have strong intrinsic motivation, and extrinsic motivation as supporter. Individuals must have skills to support their creativity, as well as literacy, knowledge, technique, and interpersonal skills. Second, the process is a way of thinking to solve problems (clarifier, ideator, developer, and implementer). Third, press is support from the environment, as well as superiors, colleagues, resources, best practices and so on. Fourth, product of creativity in the form of ideas, physical objects, and processes/methods. The form of creativity products in learning activities are in the form of learning media, learning methods, and educational props. Understanding four aspects of creativity will give new and fresh idea to make creative learning for children, so that children will enjoy the learning activities and become creative students.